Perlindungan Hukum Terhadap Konsumen Atas Barang Tiruan Yang Marak Dijual Di E-Commerce - Dinar Aisyah Pratiwi; Rina Arum Prastyanti (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Rapid developments in today's life, especially in the fields of technology and economics, have resulted in globalization which affects various aspects of life. Information technology, especially the internet, has changed the way humans interact, do business and transact. The phenomenon of online trading via E-commerce platforms has become rampant in various countries, enabling cross-border transactions without physical meetings between sellers and buyers. However, the impact of this convenience also includes the spread of imitation or fake products which are detrimental to consumers and original producers of the brand. This research is normative research with a descriptive qualitative approach. With sources taken from books, journals, laws and regulations, and literature relevant to the research. The results obtained are that business actors have the right to be responsible to consumers for counterfeit goods which result in losses for consumers.